New molecular data attest to the absence of cospeciation patterns between Placobdella costata (Fr. Müller, 1846) (Hirudinea) and freshwater turtles (Emys spp.) in Italy. Issue 1 (1st January 2021) - Vecchioni, L.; Marrone, F.; Liuzzo, M.; Seglie, D.; Cavalcante, R.; Bazan, G.; Arizza, V.; Arculeo, M.
Abstract: The only Palearctic representative of the leech genus Placobdella Blanchard, 1893 is P. costata, an ectoparasite of freshwater turtles. To date, no conclusive evidence about the possible presence of coevolutionary patterns between this leech and its turtle hosts is available due to the paucity of DNA sequence data available for P. costata ; moreover, comparative host data is also mostly lacking, making any inferences more difficult. The discovery of new populations of the species in northern Italy and Sicily allowed us to generate novel mitochondrial DNA sequences and to compare the topology of the resulting phylogenetic trees with the phylogeny of the turtle hosts occurring in the study area, i.e., Emys orbicularis and E. trinacris . The branching pattern of the phylogenetic tree for P. costata is not congruent with that of its turtle hosts, thus suggesting the lack of coevolutionary or cospeciation phenomena between these taxa. The lack of a coevolutionary pattern might be ascribed to the different dispersal ability of Placobdella costata and Emys spp. and to the host generality of the leech, as confirmed by the occurrence of P. costata on aquatic turtles belonging to the genus Mauremys in areas where Emys spp. are rare or absent. A single leech cytochrome c oxidase subunit 1 haplotype was found in each study region, and the overall nucleotide diversity was very low throughout the investigated distribution. This apparent lack of a clear phylogeographical pattern was unexpected in the P. costata populations occurring in the circum-Mediterranean areas, where the occurrence of high haplotype and nucleotide diversity is customary for most terrestrial and freshwater species. Based on the available data, we suggest a recent, post-glacial origin of the studied P. costata populations.